Between Culture and Choice: Mediating Role of Personal Preference in Hijab-Wearing Practices in Pakistani Higher Education Institutions - Muhammad Shahzad; Laraib Fatima; Sidra Batool; Kirn Ashraf (Journal of Religion and Society, 2025)
This study assessed the mediating role of personal preference in the association between cultural influence and hijab-wearing practice among female students in Higher Education Institutions. The study addresses the pressing need to understand the complex dynamics surrounding the practice of wearing the hijab in various educational and cultural situations. 350 respondents were selected from two public sector Higher Education Institutions (HEI) by employing convenient sampling technique. Data were collected using a well-structured research survey. It had questions pertaining to the study variables. The collected data were analysed using Smart PLS 4 and PROCESS Macro. The key finding of the study shows that personal preference mediates the relationship between cultural influence and hijab wearing practice. The study concludes that for the comprehensive understanding of the hijab wearing practices, it is necessary to take into account both cultural influence and personal preference. The study has wider ramifications for policy making, cultural awareness and inclusive environment at HEIs. Keywords: Personal Preference, Mediating Role, Hijab-Wearing Practice, Higher Education Institutes (HEI), Cultural Influence